Distribution of de novo Donor-Specific Antibody Subclasses Quantified by Mass Spectrometry: High IgG3 Proportion Is Associated With Antibody-Mediated Rejection Occurrence and Severity - Pernin, Vincent; Beyze, Anais; Szwarc, Ilan; Bec, Nicole; Salsac, Céline; Perez-Garcia, Esther; Mourad, Georges; Merville, Pierre; Visentin, Jonathan; Perrochia, Helene; Larroque, Christian; Couzi, Lionel; et al. (Frontiers in Immunology, 2020)
Donor-specific antibodies (DSA) are the main risk factor for antibody-mediated rejection (ABMR) and graft loss but could have variable pathogenicity according to their IgG subclass composition. Luminex-based test might lacks sensitivity for the detection of IgG subclasses and this test does not allow quantifying the relative abundance of each IgG subclass. We investigated the precise repartition of each DSA subclass and their role in ABMR occurrence and severity, using an innovative mass spectrometry-based method. Between 2014 and 2018, we enrolled 69 patients who developed de novo DSA (n=29 without ABMR, and n=40 with ABMR) in two transplant centers. All IgG subclasses were detected in every samples tested: 62.7% were IgG1, 26.6% IgG2, 6.6% IgG3, and 4.2% IgG4. The IgG3 proportion was significantly higher in the ABMR + compared to ABMR- group (8.4% vs 5.6%, p=0.003). The proportion of IgG1, IgG2 and IgG4 of DSA was similar between the two groups. Higher IgG3 level was associated with higher C4d deposition, higher microvascular inflammation scores, and glomerular filtration rate decline >25%. IgG3 proportion was not correlated with DSA MFI. Multivariate analysis showed that proteinuria and high level of IgG3 DSA were the only two factors independently associated with ABMR. In conclusion, de novo DSA are always composed of the four IgG subclasses, but in different proportions. High IgG3 proportion is associated with ABMR occurrence and severity and with poorer outcome, independently of DSA MFI.